Effects of Effleurage Massage in Reducing Pain in Intranatal Patients - Arsyifa Inneza Hermoko; Sulastri Sulastri (Contagion: Scientific Periodical Journal of Public Health and Coastal Health, 2023)
At the time of labor the mother experiences pain, pain during childbirth is felt by the mother due to uterine contractions. Massage is an act of producing relaxation and improving circulation so as to reduce pain. The purpose of the research to determine the effect of massage effleurage technique on the pain of active phase maternity mothers. Research is quantitative research with the Quasy Experiment method. The design of this study is one group pretest posttest design. The sampling technique in this study was total sampling. The sample in this study was 30 pregnant women who experienced labor pain during the 1st active phase. The instrument used in data collection in this study used a Numeric Rating Scale (NRS) observation sheet. The patient will be given an effleurage massage for 15 minutes, Data analysis using paired sample test. The results of the analysis found that the average value of pain at the time of pretest measurement was 2.27 (0.64), while in the posttest measurement, the average value of pain was 1.30 (0.46). The mean difference between pretest and posttest measurements was recorded at 0.96 with a confidence interval (95% CI) of 0.784; 1.150. The statistical results show a value of p = 0.001. Providing intervention in the form of massage effleurage in intranatal patients when 1 is active can help provide comfort so as to reduce the pain felt. Keyword: Complementary Therapy, Intranatal Patient, Massage Effleurage, Pain